Mental Illness in Singapore: A History of a Colony, Port City, and Coolie Town. Issue 2 (1st June 2016) - Loh, Kah Seng
Abstract : The case of Singapore explores the history of mental illness in a British colony, port city, and Chinese coolie town. As a colony, Singapore not only received Western psychiatric expertise from the metropole but also suffered from the inner contradictions and failings of colonial rule. The mental asylum thus had a both modernizing and marginal role. As an international port city, Singapore was a major center for internationally crisscrossing flows, yet the transnationalism in mental health policy remained connected to colonial power in two ways: the British simplified the culturally diverse patients into distinct, subordinate races and transferred them between Singapore and other countries. Singapore was also an unruly "coolie town" where, utilizing the weapons of the weak, Chinese sufferers contested the psychiatric regime in the asylum and continued to seek treatment and care beyond it. Their ability to do so depended, however, on the specific circumstances that prevailed in the individual, asylum, and coolie town, and their agency was expressed in relation to the colonial system rather than independent of it.